Protection against acute cerebral ischemia/reperfusion injury by QiShenYiQi via neuroinflammatory network mobilization - Wang, Yule; Xiao, Guangxu; He, Shuang; Liu, Xinyan; Zhu, Lin; Yang, Xinyue; Zhang, Yiqian; Orgah, John; Feng, Yuxin; Wang, Xiaoying; Zhang, Boli; Zhu, Yan (Biomedicine & pharmacotherapy, 2020)
[Display omitted] Cerebral ischemia/reperfusion injury (CI/RI) is a common feature of ischemic stroke, involving a period of impaired blood supply to the brain, followed by the restoration of cerebral perfusion through medical intervention. Although ischemia and reperfusion brain damage is a complex pathological process with an unclear physiological mechanism, more attention is currently focused on the neuroinflammatory response of an ischemia/reperfusion origin, and anti-inflammatory appears to be a potential therapeutic strategy following ischemic stroke. QiShenYiQi (QSYQ), a component-based Chinese medicine with Qi-tonifying and blood-activating property, has pharmacological actions of anti-inflammatory, antioxidant, mitochondrial protectant, anti-apoptosis, and antiplatelet aggregation. We have previously reported that the cardioprotective effect of QSYQ against ischemia/reperfusion injury is via improvement of mitochondrial functional integrity. In this research work, we aimed to investigate the possible mechanism involved in the neuroprotection of QSYQ in mice model of cerebral ischemia/reperfusion injury based on the inflammatory pathway. The cerebral protection was evaluated in the stroke mice after 24 h reperfusion by assessing the neurological deficit, cerebral infarction, brain edema, BBB functionality, and via histopathological assessment. TCM-based network pharmacology method was performed to establish and analyze compound-target-disease & function-pathway network so as to find the possible mechanism linking to the role of QSYQ in CI/RI. In addition, RT-qPCR was used to verify the accuracy of predicted signaling gene expression. As a result, improvement of neurological outcome, reduction of infarct volume and brain edema, a decrease in BBB disruption, and amelioration of histopathological alteration were observed in mice pretreated with QSYQ after experimental stroke surgery. Network pharmacology analysis revealed neuroinflammatory response was associated with the action of QSYQ in CI/RI. RT-qPCR data showed that the mice pretreated with QSYQ could significantly decrease IFNG-γ, IL-6, TNF-α, NF-κB p65, and TLR-4 mRNA levels and increase TGF-β1 mRNA level in the brain compared to the untreated mice after CI/RI (p < 0.05). In conclusion, our study indicated the cerebral protective effect of pretreatment with QSYQ against CI/RI, which may be partly related to its potential to the reduction of neuroinflammatory response in a stroke subject.